1997
DOI: 10.1021/jp970309d
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical and Photoluminescence (PL) Properties of p-Type Porous Silicon/Electrolyte Solution Interface:  Potential Dependent PL Spectra as a Result of Size Dependent Quenching

Abstract: Potential dependences of the photocurrent and visible photoluminescence (PL) from p-type porous silicon (p-PS) in 0.2 M Na 2 SO 4 aqueous solution were investigated. When the potential became more negative than -0.6 V, a cathodic photocurrent was observed and PL was quenched. When the potential was swept back in the positive direction, the PL intensity increased, the photocurrent decreased, and both returned to the initial values. PL spectra measurements showed that the quenching of the PL intensity was accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The ZnO spectro-electrochemical dissolution could result from a reverse electrosynthesis reaction at positive potentials under UV illumination. Similar photoelectrochemical dissolution reactions have been previously repoted …”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The ZnO spectro-electrochemical dissolution could result from a reverse electrosynthesis reaction at positive potentials under UV illumination. Similar photoelectrochemical dissolution reactions have been previously repoted …”
Section: Resultssupporting
confidence: 56%
“…To obtain direct evidence of the influence of the surface depletion layer on the relative intensity of the visible band and discard the influence of other chemical, structural, or geometrical parameters, the PL properties of ZnO:Cl NWs were characterized while adjusting their surface band bending by means of an applied potential. For this purpose, the ZnO:Cl NWs were immersed inside a quartz electrochemical cell filled with a 0.1 M Na 2 SO 4 aqueous solution as electrolyte. A potential was applied using a three-electrode potentiostat system with an Ag/AgCl electrode in saturated KCl (3 M) as the reference electrode and a Pt wire as counter electrode (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our model hydrogen is necessary to ensure hole injection from S 2 O 8 2- and thus light emission. The importance of hydrogen is also clear from work of Uosaki and co-workers, who report a quenching at negative potentials of the photoluminescence from p-type porous silicon due to illumination with short-wavelength light (<400 nm). The decrease in emission coincides with the onset of cathodic photocurrent due to hydrogen evolution; i.e., luminescence and photocurrent characteristics are correlated.…”
Section: A Hydrogen-based Modelmentioning
confidence: 92%
“…[11][12][13][14] Most of the studies reported so far have concentrated on the PL properties of PS. [15][16][17][18][19][20][21][22] Electroluminescence (EL) is, however, more important as far as technological application is concerned. In this respect, Koshida and Koyama demonstrated that a transparent metal/PS/p-Si/Al cell emits EL (orange) at relatively low applied voltage, although the quantum efficiency was quite low (<10 Ϫ5 %).…”
mentioning
confidence: 99%